Orthodontic view in the diagnoses of obstructive sleep apnea - Saeed M Banabilh (Wolters Kluwer Medknow Publications, 2017)
Obstructive sleep apnea is an exciting area for orthodontists to be involved. The level of awareness of sleep apnea and related health issues is growing rapidly. The demand of integrating sleep into the orthodontic practice shortly will be driven by the need of the societies as some of our patients will be shortly coming into our offices aware of sleep apnea. However, with our busy clinical orthodontic practice, the need of condense short review become more demanding. Therefore, this review will try to summarize the clinical and orthodontic observation in the diagnoses of adult obstructive sleep apnea with clinical application in orthodontic practice.